2018
DOI: 10.1186/s12199-018-0748-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of molar incisor hypomineralization and regional differences throughout Japan

Abstract: BackgroundMolar incisor hypomineralization (MIH) frequently occurs in children worldwide. However, MIH prevalence throughout Japan has not yet been investigated. The purpose of this study was to clarify MIH prevalence rates and to consider potential regional differences throughout Japan.MethodsA total of 4496 children aged 7–9 years throughout Japan were evaluated in this study. MIH prevalence rates among children were evaluated in eight regions throughout Japan. A child’s residence was defined as the mother’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
4
13
0
1
Order By: Relevance
“…However, our results were found to be lower than those reported in Lebanon (26.7%) [ 27 ] and Dubai (27.2%) [ 28 ] but higher than those reported from Nigeria (17.7%) [ 17 ], Kenya (13.7%) [ 16 ], Libya (2.9%) [ 15 ] and Egypt (2.3%) [ 18 ]. There was no difference in the occurrence of MIH with age in this study, in line with results reported by Oydele et al [ 17 ] and Ghanim et al, [ 29 ] but in contradiction with studies that showed significant increase with age by Da costa-Silva et al [ 30 ] and the decrease of MIH with age by Saitoh et al [ 24 ]. In terms of gender, the current study showed boys had slightly higher MIH prevalence than girls, although this was not statistically significant, just as some studies have indicated before [ 24 , 27 ] but contrary to results from other studies where the prevalence were higher for girls [ 16 ] and for boys [ 31 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, our results were found to be lower than those reported in Lebanon (26.7%) [ 27 ] and Dubai (27.2%) [ 28 ] but higher than those reported from Nigeria (17.7%) [ 17 ], Kenya (13.7%) [ 16 ], Libya (2.9%) [ 15 ] and Egypt (2.3%) [ 18 ]. There was no difference in the occurrence of MIH with age in this study, in line with results reported by Oydele et al [ 17 ] and Ghanim et al, [ 29 ] but in contradiction with studies that showed significant increase with age by Da costa-Silva et al [ 30 ] and the decrease of MIH with age by Saitoh et al [ 24 ]. In terms of gender, the current study showed boys had slightly higher MIH prevalence than girls, although this was not statistically significant, just as some studies have indicated before [ 24 , 27 ] but contrary to results from other studies where the prevalence were higher for girls [ 16 ] and for boys [ 31 ].…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of MIH in the current study was 20.1%, which was higher than the mean global prevalence (13.1% to 14.2%) reported in 2018 [13,14], but comparable to results reported in Spain (21.8%) [23], Japan (19.8%) [24], Thailand (20.0%) [25], Iran (20.2%) [26] and Iraq (21.5%) [19]. However, our results were found to be lower than those reported in Lebanon (26.7%) [27] and Dubai (27.2%) [28] but higher than those reported from Nigeria (17.7%) [17], Kenya (13.7%) [16], Libya (2.9%) [15] and Egypt (2.3%) [18].…”
Section: Prevalence Of Mihsupporting
confidence: 68%
“…The evidence that MIH frequency varies across the world [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] is supported by the results found in the present study. The association found in the Turkish population was different from the results obtained in the cohorts from Brazil, which indeed indicates that genetic factors contributing to the MIH phenotype may vary depending on geographic origin.…”
Section: Plos Onesupporting
confidence: 83%
“…These asymmetrical lesions affect the first permanent molars, usually with the permanent incisors [4], and more recently MIH has been reported to affect canines too [5]. Prevalence of MIH varies but has been consistently reported to range between 1% and 35% in all parts of the world, with most reported frequencies around 12% [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…No difference in the occurrence of MIH with age in this study, in line with results reported by Oydele et al (15), and Ghanim et al, (28) but in contradiction with studies that showed signi cant increase with age by Da costa-Silva et al (29) and decrease with age by Saitoh et al (23). In terms of gender, the current study showed boys had slightly higher MIH prevalence than girls, although this was not statistically signi cant, just as some studies have indicated before (23,26) and contrary to results from other studies where the prevalence were higher for girls (14) and for boys (30).…”
Section: Prevalence Of Mihsupporting
confidence: 81%